EVOLUTION OF THE CORPORATE SOCIAL RESPONSIBILITY PARADIGM (Economic journal of Lesya Ukrainka Volyn National University, 2025)
The processes of globalization motivate Ukraine, despite the military actions, to transition to sustainable economic development. The European integration ambitions of our country require the implementation of modern interaction practices between state and business, as well as between business and society, which would strengthen the mutual responsibility of all participants in business processes and public life, considering the environmental impact.Today, the concept of ‘corporate social responsibility’ (CSR) in its various meanings, dimensions and aspects has become widespread in the global community. Along with the CSR concept, other concepts and approaches have also been developed, sometimes moving in parallel, complementing or stemming from each other, such as sustainable development, circular economy, industry 5.0, compliance, and the concept of environmental, social, and governance (ESG).To better understand the modern expressions and forms of practical reflection of the CSR concept in economic processes, it is necessary to analyze its genesis and evolution. After all, different time periods and realities had their impact on the formation and modification of the essence and objectives of this concept, as well as its transformation from customs and rules of behaviour in society to a formalized, clearly structured, concept and philosophy of doing business.This research is aimed to analyze the evolution of the concept of corporate social responsibility, its adaptation to a changing external environment and to the challenges of a particular historical period. A special focus is also made on the phrasing of the definition of corporate social responsibility.In the course of the research, the authors used the method of analysis, in particular, such varieties as historical (retrospective) and comparative analysis.The origins of the social component in corporate behaviour are quite deep and can be traced back to ancient Roman law, English law in the Middle Ages, and Christian religious philosophy in the 18th and 19th centuries. In general, it can be stated that the concept of CSR itself emerged in the United States at the end of the XIX century, but due to World War II, it was not of great interest to society until 1950-1960. From ‘business responsibility’ to the complex concept of ‘Corporate Social Responsibility’ (in various relations with many other concepts), as it is understood today, the development of CSR has passed through various time stages.With all the definitions of the CSR concept in mind, as well as related and similar or complementary concepts, it is really difficult to formulate a single, universal and comprehensive definition. In our opinion, CSR can be defined as a philosophy and a comprehensive approach to doing business to make a profit, taking into consideration the interests of all stakeholders (internal and external), with a clear focus on the economic, social and environmental aspects of doing business in the long term perspective and using a system of preventive measures and balances.
Keywords: corporate social responsibility (CSR), evolution, concept, behaviour, definition.